Building Madrasah Committee Synergy in Managing Effective and Resilient Skills Programs - Suratman, Suratman (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research focuses on marketing management by Islamic boarding schools to improve their image. This study used a qualitative approach with six respondents who were then analyzed and assessed for the validity of the data using triangulation techniques at Islamic boarding schools in Bantul Regency. The results of the study show that: 1) the management of education service delivery at Islamic boarding schools has been running effectively, as evidenced by the increase in students every year; 2) factors that enhance the image of Islamic boarding schools include community support, the role of large foundations, and the commitment of Islamic boarding schools; 3) these factors are strengthened by the 4P concept of marketing mix strategy: product, promotion, process, and people; 4) media activities have an essential role during the marketing process; 5) special programs in Islamic boarding schools can also increase public interest; 6) the characteristics of each pesantren are the main attraction for the community's interest in pesantren. Furthermore, the image of the Islamic boarding school can be formed by implementing a marketing strategy by utilizing the marketing mix concept and can be built through good communication in every coordination.